Digital labour platforms as shock absorbers: Evidence from COVID-19 - Sam Jones; Ivan Manhique (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Digital labour platforms have grown five-fold over the last decade, enabling significant expansion in gig work worldwide. We interrogate the criticism that these platforms tend to amplify aggregate economic shocks for registered users (workers). Based on the universe of records from a matching platform for informal sector manual freelancers in Mozambique, we analyse how task supply and demand altered with the onset of COVID-19. Treating the pandemic as a structural break, which extends to an event study analysis, we find it was associated with a net increase in tasks demanded per worker, but no clear change in supply growth (new registrations). These trends are evident across multiple market segments, including female-dominated professions, suggesting digital labour markets can help workers adjust to economic shocks in low-income contexts.
Keywords: J23; J46; O17; 330; COVID-19; digital labour markets; economic shocks; freelancers; Mozambique